Association Between Exclusive Breastfeeding and Type 1 Diabetes Mellitus - Saad Farid, Mazhar Ali, Fazal Badshah, Sumbal Afzal Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to determine the association of formula milk and exclusive breastfeeding (EBF) with type 1 diabetes (TID) in children. Methods: This epidemiology cross-sectional study was conducted in Saidu Teaching Hospital from January-2022 to January-2023. We included 75 patients with diagnosis of TID who presented in diabetes clinic of the hospital. For control group we included 75 children who did not had T1D. Data regarding type of feeding was collected from parent of each child. Results: Mean age was 7.89±2.1 years in patients with T1D and 8.1±1.9 years in control group (p-value 0.52). There were 40 (53.3%) male patients in T1D and 39 (52%) male patients in control group (p-value 0.87). There was very low percentage of exclusive breastfeeding (EBF) in T1D patients; 9 (12%) only in comparison to 43 (57.3%) in controls (p-value <0.001). There was high prevalence of formula feeding in T1D patients; 31 (41.3%) in comparison to 12 (16%) in controls (p-value <0.001). Conclusion: In present study, the frequency of EBF was significantly lower in T1D patients in comparison to controls. So EBF seems to be a protective factor against occurrence of type 1 diabetes. Keywords: Exclusive breastfeeding, Type 1 diabetes, formula feeding.